Blue Light Laser Results in Less Vocal Fold Scarring Compared to KTP Laser in Normal Rat Vocal Folds. (4th August 2020) - Lin, R. Jun; Iakovlev, Vladimir; Streutker, Catherine; Lee, Daniel; Al‐Ali, Mohammed; Anderson, Jennifer
Abstract : Objectives: Preliminary investigations suggest that a novel blue light (BL) laser with a wavelength of 445 nm is comparable to the commonly utilized potassium titanyl phosphate (KTP) laser (532 nm) for treatment of various laryngeal pathologies. The objective of the current study is to make a direct histological comparison of the degree of vocal fold scarring after either BL or KTP laser treatment in an animal model. Study Design: This was a randomized controlled study using rats. Methods: Twenty‐four Sprague–Dawley rats were randomized to BL or KTP laser treatment. Laser was delivered in non‐overlapping pulses to normal rat vocal folds. Larynges in each group were harvested at three time points: post‐operative day 1, 30, and 90. Three animals served as negative controls. The excised whole larynges were sectioned transversely and stained with hematoxylin/eosin and trichrome. Presence of subepithelial inflammation and protein deposition/fibrosis indicative of scarring were scored semi‐quantitatively (from grade 1–3) by two pathologists blinded to treatment groups. Results: Between‐group comparison showed that both laser treatments resulted in significantly elevated subepithelial protein deposition/fibrosis 90 days after treatment compared to negative controls (BL: 2 ± 0; KTP: 2.67 ± 0.29; control: 1.17 ± 0.29; P < .05). However, the degree of protein deposition/fibrosis was significantly higher in the KTP group compared to the BL group ( P = .016). Within‐group comparison showed that the KTP group showed evidence of fibrosis as early as 30 days after treatment, which was not observed in the BL group. Conclusions: The current study suggests that the degree of scarring is significantly less after BL laser treatment compared to KTP in normal rat vocal fold tissue. Level of Evidence: NA Laryngoscope, 131:853–858, 2021